A grounded theory of value dissonance in strategic relationships. Issue 4 (December 2016) - Pinnington, Bruce D.; Meehan, Joanne; Scanlon, Tom
Abstract: Value creation is central to major business-to-business relationships, yet despite the criticality, stakeholder value expectations may not be met. This study explores how senior buyer and seller-side relationship managers (N=25), managing relationships worth £5M–£750M per annum, perceive and manage value and the implications of these perceptions to both parties. In a novel combination, focus groups were used to generate the initial dataset and category structure of a grounded theory study. Categories were subsequently explored through 1:1 interviews. The concept of Internal Value Perception Dissonance (IVPD) is developed, and its properties, dimensions and consequences are discussed. IVPD adds a new intra-organisational dimension to the causes of relational failure. Value-dissonance theory is developed that directs practitioners toward pluralistic, internal collaboration as a precursor to inter-organisational collaboration. The disparity in buyer-side value perceptions, shows that these organisations cannot be regarded as cohesive, unitary entities. The buyer does not exist in these cases. Highlights: Internal Value Perception Dissonance (IVPD) theory developed using grounded theory. IVPD identifies intra-organisational dimensions of relational failure. Internal buyer-side alignment is a precursor to inter-organisational value. Value-dissonance theory directs practitioners toward pluralistic value assessments.